The healthy green drink diet : advice and recipes for happy juicing - Manheim, Jason (New York : Skyhorse Pub., 2012)
One juice or smoothie a day made from green vegetables such as kale, cucumber, celery, and spinach works wonders for organ health, immune system strength, and weight loss. Now the founder of heathygreendrink.com offers a persuasive argument for adding a green drink to your day, as well as recipes for dozens of different variations.
Includes bibliographical references (p. 162) and index.
Keywords: Vegetable juices; Smoothies (Beverages); Cookbooks